Self-Biasing High Precision CMOS Current Subtractor for Current-Mode Circuits - (:unkn) unknown (UNIV SUCEAVA, FAC ELECTRICAL ENG, 2013)
In this study, a novel, differential pair based, high performance and high bandwidth current subtractor is proposed. Very low equivalent impedances are obtained at input ports n and p by using source follower transistors. Furthermore, the proposed circuit is self-biasing which makes it resistant to process, supply voltage and temperature variations. The proposed current subtractor can be used as an input stage for current-mode active circuits like current differencing buffered amplifier (CDBA), operational transresistance amplifier (OTRA) and current differencing transconductance amplifier (CDTA) which employ current subtractors. A numeric figure-of-merit is defined and it is used to demonstrate the superior performance of the proposed circuit.
Keywords: CDBA; CDTA; current subtractor; self-biasing; OTRA; DIFFERENCING BUFFERED AMPLIFIER; INDUCTANCE CIRCUITS; DESIGN